MANTLE UPWELLING AND MELTING BENEATH SLOW SPREADING CENTERS: EFFECTS OF VARIABLE RHEOLOGY AND MELT PRODUCTIVITY - Choblet G.; Parmentier E.M. (My University, 2001)
We examine the effects of non-uniform rheology and melting models on the 3D structure of mantle upwelling beneath spreading centers. Our numerical models identify a range of conditions for which 3D upwelling can be considered as a possible mechanism for magmatic segmentation of slow spreading ridges. In a highly viscous shallow region due to dehydration of the solid by melt extraction, flow results essentially from the plate spreading. This contrasts with a deeper, buoyant, low viscosity region, where melt is present but upwelling solid is not yet dehydrated, and where both solid and melt flows acquire their 3D nature. The thickness of this buoyant region, depending mainly on the temperature interval between the wet and dry solidi, results in a specific characteristic length scale for the upwelling. Smaller segmentation wavelengths occur for smaller values of this thickness. In contrast to isoviscous models where minimum segmentation wavelengths were large (>150 km), minimum wavelengths obtained in models with non-uniform rheology and melt production (40-70 km) are comparable to smallest observed segment lengths. A single wavelength may be preferred for a given set of parameters, but such a preferred wavelength is difficult to achieve because a range of initially prescribed wavelengths can persist for long times. The persistence of 3D solutions for tens of millions of years of model time indicate that segment lengths observed at slow mid-ocean ridges may be inherited from the initial stages of spreading.
Keywords: MID-OCEAN RIDGES; MANTLE; RHEOLOGY; MELT; MAGMATIC SEGMENTATION